(untitled) (Research, Society and Development, 2020)
This article has as its object of study the theme of Autistic Spectrum Disorder at school, in which it is carried out through a bibliographic research, of an analytical descriptive character and based on the existing literature by several authors that contextualizes Autistic Spectrum Disorder at school. With the general objective of analyzing autistic spectrum disorder at school through this analysis of theoretical framework. Presented as specific objectives: the study of Autism, its principle and concept; the concept of defining Autism; and the school space and regular education for the Autistic student. The results produced by the research show what the school can offer in education and inclusion in relation to autism, making social integration possible, the inclusion of students with autism spectrum disorders in the educational field, as social coexistence will facilitate access to goods and collective services, eliminating obstacles and forms of discrimination.